By Students, for Students: Student-Created Open Educational Resources. Issue 1 (4th May 2022) - Oakleaf, Linda; Dodd, Regan
Abstract: Online textbooks or Open Educational Resources (OER) have become more popular in recent years due to the rising costs of textbooks. Unfortunately, few OER currently exist that address topics in recreation, sport, tourism, or leisure management. Most OER are written by faculty, but DeRosa argued that it could benefit students to write their own OER. When students write their own textbook, this has the potential to increase students' understanding of course content and to improve their writing skills. This article provides a blueprint for pursuing this project with undergraduate students, while highlighting both the benefits and the pitfalls.